Subfossil remains of Peromyscus stirtoni (Mammalia: Rodentia) from Costa Rica - Woodman, Neal (Revista de Biología Tropical, 1988)
Preliminary sampling of near-surface sediments from Caverna Ojos Verdes, Barra Honda National Park, Costa Rica, yielded remains of the white-footed mouse, Peromyscus stirtoni, which was not reported previously from this country. Remains of other animals recovered from the cave sediments include fish, amphibians, reptiles, birds, and fourteen taxa of mammals. The mammalian fauna is dominated by forest species. The environment which existed when the remains of these animals were deposited in the cavern was probably dry tropical forest, similar to that which occurs on Cerro Barra Honda today. Actual age of the sediments in unknown, but tiny fragments of pottery in some levels suggests middle to late Holocene. The occurrence of P. stirtoni probably represents a pre-Columbian distribution in a dry forest habitat which has since been mostly lost due to clear-cutting for agriculture.